Wind power potential assessment for three locations in Algeria - Rehman, Shafiqur (2020)
This paper utilized wind speed data over a period of almost 10 years between 1977 and 1988 from three stations, namely Adrar, Timimoun and Tindouf to assess the wind power potential at these sites. The long-term annual mean wind speed values along with the wind turbine power curve values were used to estimate the annual energy output for a 30 MW installed capacity wind farm at each site. A total of 30 wind turbines each of 1000 kW rated power were used in the analysis. The long-term mean wind speed at Adrar, Timimoun and Tindouf was 5.9, 5.1 and 4.3 m/s at 10 m above ground level (AGL), respectively. Higher wind speeds were observed in the day time between 09:00 and 18:00 h and relatively smaller during rest of the period. Wind farms of 30 MW installed capacity at Adrar, Timimoun and Tindouf, if developed, could produce 98,832, 78,138 and 56,040 MWh of electricity annually taking into consideration the temperature and pressure adjustment coefficients of about 6% and all other losses of about 10%, respectively. The plant capacity factors at Adrar, Timimoun and Tindouf were found to be 38%, 30% and 21 %, respectively. Finally, the cost of energy (COE) was found to be 3.1, 4.3 and 6.6 US cents/kWh at Adrar, Timimoun and Tindouf, respectively. It was noticed that such a development at these sites could result into avoidance of